VOC dan Dinamika Kekuasaan di Sumenep Abad XVIII: Sebuah Tinjauan Historis - Qalbiyah, Syifaul; Wijaya, Daya Negri (Jayapangus Press, 2024)
The city of Sumenep is a traditional palace city which is located on the outskirts of the city and also close to the beach. The Palace City has the function of being the residence of kings and their families, and has a role as a place for cultural activities, government activities and the economy. Since 1705, after Sumenep came under the auspices of the VOC, elements of foreign culture began to enter into the formation of the city of Sumenep. The general aim of this research is to describe incidents or events in the past, and then use them for the learning process in the present. The research method used in this research is the historical research method which consists of five stages, first topic selection, second heuristics, third source criticism, fourth interpretation, and fifth historiography. Sumenep is located at the tip of Madura Island and occupies a strategic position that supports Sumenep as a stopping area which is often visited by ships and boats from the archipelago or from abroad. In 1705, when Mataram entered into an agreement, Sumenep as a whole became colonial territory and Sumenep was a busy trade center in the 18th century because it had a port as a stopping area for ships connecting with islands in the eastern region and had an important port for trade over long distances. Thus, the release of the Sumenep area from Mataram's control would certainly go through a long process. One of the influencing factors is the existence of an element of interest in maintaining the power that has mastered this issue.